Education and its construction - Bermejo, Lucas Justiniano; Cruz, José Anderson Santos; Bizelli, José Luís; Lemes, Sebastião de Souza (Revista Hipótese, 2018)
Brazilian education has traits of the Jesuit model, centered on the reproduction of information, which does not contribute to the critical and reflexive stimulus in the construction of knowledge. However, there are many elements that cross the construction of knowledge, such as politics, economics, philosophy, history of education and the country that contribute to the delineation of Brazilian education. The current educational model needs to be reformed so that the subject can be trained so that it is critical and that it can reflect in a more conscious way and that it can understand the best paths for itself. Thus as a result there are no elements that can produce social elements with critical, reflexive or political capacity. This depoliticization experienced today in the educational sphere conflicts with facticity versus validity. Therefore, the discussion is based on the reform of education based on the experience of school reality.